Influence of Water Availability on Yield of Cowpea Under Rainfed Conditions - Ramana Rao, B V; Ramakrishna, Y S; Daulay, H S (Annals of Arid Zone, 2016)
The variation in the yield of cowpea crop as influenced by the weekly water availability conditions were analysed and reported. The correlation coefficient between the crop yield and mean AE/PE during the reproductive stage was found to be 0.98. A second degree regression equation was also fitted for the yield using the mean AE/PE values during the reproductive stage.